The Factors that Affect the Profitability of Banks Listed on the Indonesia Stock Exchange - et. al., Muhammad Bayu Aji Sumantri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to study the factors that affect the profitability of banking sector companies listed on the Indonesia Stock Exchange. The object of this research is banks listed on the Indonesia Stock Exchange in the 2015-2019 period. The factors used in this study are financial factors in the form of financial ratios reported by the company in its annual report. In this study, the dependent variables used are Earning Per Share (EPS), Debt to Equity Ratio (DER), and Price to Book Value (PBV). For the independent variable used is Return on Equity (ROE). This study uses multiple linear regression analysis with panel data analysis techniques. This study found that Earning Per Share (EPS), Debt to Equity Ratio (DER) and Price to Book Value (PBV) significantly influence Return on Equity